Forensic efficiency evaluation of a novel multiplex panel of InDels and STRs in the Guizhou Han population and its phylogenetic relationships with other reference populations - Yanhua Zheng; Ting Wang; Kun He; Yunteng Yang; Jiangtao You; Xiaolan Huang; Hongling Zhang; Zheng Ren; Qiyan Wang; Jiang Huang; Xiaoye Jin (Taylor & Francis Group, 2023)
Background Insertion/deletion polymorphism (InDel), as the third genetic marker, has been given a lot of attention by forensic geneticists since it has the advantages of extensive distributions in the human genome, small amplicon, and low mutation rate. However, the extant InDel panels were only viewed as supplemental tools for kinship analyses. In addition, these panels were not conductive to mixture deconvolution because InDels in these panels mainly displayed two alleles. Aims The purpose of this study is to investigate genetic distributions of a novel panel of InDels and STRs in the Guizhou Han population; assess the forensic application value of the panel; and conduct population genetic analyses of the Guizhou Han and other reference populations based on the overlapping loci. Subjects and methods The bloodstain samples of 209 Guizhou Han were gathered and genotyped by the novel panel. Allelic frequencies and forensic parameters of two miniSTRs and 59 InDels in the panel were estimated. In addition, we assessed phylogenetic relationships among the Guizhou Han and other reference populations by principal component analysis, DA genetic distance, and neighbor-joining tree. Results A total of 139 alleles of 61 loci could be observed in the Guizhou Han population. Polymorphic information content values of 59 InDels were greater than 0.3 in the Guizhou Han population. The cumulative power of discrimination and probability of exclusion of two miniSTRs and 59 InDels in the Guizhou Han population were 0.999999999999999999999999997984 and 0.9999986, respectively. Principal component analysis of 14 populations showed that the Guizhou Han population located closer to Hunan Han and Southern Han Chinese (CHS) populations. Similar results were also discerned from DA genetic distances and the neighbor-joining tree. Conclusion To sum up, the novel panel could be employed for forensic personal identification and paternity testing in the Guizhou Han population as a promising independent tool. Besides, the principal component analysis and phylogenetic tree of the Guizhou Han and other compared populations revealed that the Guizhou Han population possesses close genetic affinities with Hunan Han, CHS, and Han Chinese in Beijing (CHB) populations.